The impact of mentoring on public services and the civilian population ("Journal "U". Economy. Management. Finance.", 2024)
This year, a special platform was launched that brought together mentors and organizations from various fields of activity to find effective skills and competencies, and transfer culture, mentoring experience, and moral guidelines from professionals to ordinary citizens for personal and career growth. The new direction was a response to a request from Russians who are looking for an opportunity to become a mentor or want to receive mentoring assistance.
Keywords: mentoring; public service; civil servant; training